A weakly over-penalized symmetric interior penalty method - Brenner, Susanne C; Owens, Luke; Sung, Li-Yeng (Electronic transactions on numerical analysis, 2008)
We introduce a new symmetric interior penalty method for symmetric positive definite second order elliptic boundary value problems, where the jumps across element boundaries are weakly over-penalized. Error estimates are derived in the energy norm and the [L.sub.2] norm for both conforming and nonconforming meshes. Numerical results illustrating the performance of the method are also presented. Key words. symmetric interior penalty method, weak over-penalization AMS subject classifications. 65N30